2015
DOI: 10.1111/evo.12707
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ecological dominance of yeast species in high‐sugar environments

Abstract: In budding yeasts, fermentation in the presence of oxygen evolved around the time of a whole genome duplication (WGD) and is thought to confer dominance in high-sugar environments because ethanol is toxic to many species. While there are many fermentative yeast species, only Saccharomyces cerevisiae consistently dominates wine fermentations. In this study, we use co-culture experiments and intrinsic growth rate assays to examine the relative fitness of non-WGD and WGD yeast species across environments to asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 94 publications
(225 reference statements)
3
37
0
Order By: Relevance
“…; Hagman and Piskur ; Williams et al. ). Although we don't have reasons to think that this phylogeny is biased or unrepresentative, the fact that there exist more than thousands described yeasts species (see Kurtzman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Hagman and Piskur ; Williams et al. ). Although we don't have reasons to think that this phylogeny is biased or unrepresentative, the fact that there exist more than thousands described yeasts species (see Kurtzman et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Williams et al. ). These authors suggested that fermentative capacity represents an ecological innovation that triggered an adaptive radiation.…”
Section: Introductionmentioning
confidence: 99%
“…To measure fitness, we calculated the intrinsic growth rate ( r ) using the exponential growth equation (Williams et al ., ): Nt=N0*er*t Where N t is final cell density (CFU/ml), N 0 is initial cell density (CFU/ml) and t is time in hours. Fermentation time 60 h was used to estimate the intrinsic growth rate because it showed the lowest deviation among replicates.…”
Section: Methodsmentioning
confidence: 99%
“…S. cerevisiae yeasts are characterized by their high capability to ferment simple sugars into ethanol even in the presence of oxygen, known as Crabtree effect (Crabtree, ). Although, alcohol fermentation is energetically much less efficient than aerobic respiration, it provides with a selective advantage to these yeasts to outcompete other microorganisms: sugar resources are consumed faster and the ethanol produced during fermentation (Goddard, ), as well as higher levels of heat and CO 2 , can be harmful or less tolerated by their competitors (Piskur and Langkjaer, ; Piškur et al ., ; Conant and Wolfe, ; Merico et al ., ; Hagman et al ., ; Williams et al ., ). Also, nitrogen source consumption and biomass production are more efficient in S. cerevisiae (Monteiro and Bisson, ; Andorrà et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In our previous studies, it was demonstrated that vacuole of Candida species which is the storage site for plenty of nutrients 7 could serve as a niche for H. pylori, outside the human stomach. 12 Yeasts have been exploited by humans since ancient times when fermentation was the primary method to prepare and preserve foods. [8][9][10][11] Yeasts are unicellular fungi which prefer nutrient-rich environments, exhibit rapid growth and multiplication in high concentrations of simple sugars, and exhibit remarkable metabolic diversity.…”
mentioning
confidence: 99%